FORMER USM DVC-ICN DEDICATES ‘HALL OF FAME’ AWARD TO UNIVERSITY - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 6 December 2016 – The former Universiti Sains Malaysia (USM) Deputy ViceChancellor (Industry and Community Network), Dato’ Dr. Susie See Ching Mey dedicated her international award, the ‘International Adult and Continuing Education Hall of Fame’ she received at the 21st Induction Ceremony at the University of Oklahoma USA recently to USM which has contributed immensely towards it.